Short Communication: Management of patients with extensive-stage small-cell lung cancer treated with radiotherapy: A survey of practice. (2018) - Haslett, Kate; De Ruysscher, Dirk; Dziadziuszko, Rafal; Guckenberger, Matthias; Pechoux, Cecile Le; Nestle, Ursula; Slotman, Ben; Faivre-Finn, Corinne
Highlights: Increased use of thoracic radiotherapy in ES-SCLC following CREST trial. Trial schedule of 30 Gy in 10 for thoracic radiotherapy has been widely adopted. High consistency in the use of prophylactic cranial irradiation. Abstract: Objectives: The results of the randomized phase 3 CREST trial evaluating the use of thoracic radiotherapy for extensive-stage small-cell lung cancer (ES-SCLC) were published in the Lancet in 2015. The primary endpoint (10% overall survival difference at 1-year) was not achieved, but there was significant improvement in 2-year overall survival (13% vs 3%; p  = 0.004) and low toxicity rates, suggesting thoracic radiotherapy should be considered for ES-SCLC patients who respond to chemotherapy. Questions have been raised as to whether these results will lead to a change in practice. Materials and methods: We developed an electronic survey to determine the impact of the publication on clinical practice across some European countries. Results and conclusion: We report the results of our survey, which suggest the CREST trial has changed practice, resulting in an increase in the use of thoracic radiotherapy amongst the surveyed centers from 25% to 85%. Furthermore the dose and fractionation schedule used in the trial has been widely adopted across Europe.